2001
DOI: 10.1128/aem.67.4.1830-1838.2001
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Method of Determining Factors Limiting Bacterial Growth in Soil

Abstract: A technique to determine which nutrients limit bacterial growth in soil was developed. The method was based on measuring the thymidine incorporation rate of bacteria after the addition of C, N, and P in different combinations to soil samples. First, the thymidine incorporation method was tested in two different soils: an agricultural soil and a forest humus soil. Carbon (as glucose) was found to be the limiting substance for bacterial growth in both of these soils. The effect of adding different amounts of nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
94
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(104 citation statements)
references
References 37 publications
(43 reference statements)
10
94
0
Order By: Relevance
“…Seasonal changes in soil climate were further closely linked to short-and medium-term variations in resource availability, which further correlated with the quantity and quality of organic matter entering the soil, as it was also previously suggested (Bell et al, 2009;Cookson et al, 2006;Krave et al, 2002). Consequently, total bacterial communities and individual phyla studied were clearly shaped by supply of DOC, DON and mineral N (that is, ammonia, nitrate), which is in agreement with previously published data (Drenovsky et al, 2004;Zak et al, 2003;Alden et al, 2001).…”
Section: Discussionsupporting
confidence: 80%
“…Seasonal changes in soil climate were further closely linked to short-and medium-term variations in resource availability, which further correlated with the quantity and quality of organic matter entering the soil, as it was also previously suggested (Bell et al, 2009;Cookson et al, 2006;Krave et al, 2002). Consequently, total bacterial communities and individual phyla studied were clearly shaped by supply of DOC, DON and mineral N (that is, ammonia, nitrate), which is in agreement with previously published data (Drenovsky et al, 2004;Zak et al, 2003;Alden et al, 2001).…”
Section: Discussionsupporting
confidence: 80%
“…2). It has been generally accepted that carbon availability and environmental conditions are controlling microbial growth (Aldén et al, 2001;Brockman et al, 1992;Fredrickson and Balkwill, 2006;Fry et al, 1997;Jørgensen and Boetius, 2007;Whitman et al, 1998). Analyses of the organic acids in the fluids revealed that acetate seems to be the major constituent of the dissolved organic carbon (DOC).…”
Section: Discussionmentioning
confidence: 99%
“…Most known soil bacterial species are organotrophs that is, they obtain the energy for growth from the assimilation of organic compounds. However, the availability or accessibility of degradable organic compounds is limited in most soils (Alden et al, 2001;Demoling et al, 2007). In addition, there is a high degree of overlap in metabolic abilities of organotrophic bacteria (Strickland et al, 2009).…”
Section: Introductionmentioning
confidence: 99%